A Conceptual Solution of Low-CostTemperature Data Logger With Relatively High Accuracy - Medojevic, Milovan; Medojevic, Milana; Radakovic, Nikola; Lazarevic, Milovan; Sremcev, Nemanja (International Journal of Industrial Engineering and Management, 2018)
n this paper, an effort has been made to design and develop low-cost temperature data logger with relatively high accuracy. Initially,theconceptualsolutionofdatalogger consists of several elements where the main components are Arduino UnoR3 with ATmega328 microcontroller, 1-wire digital temperature sensorDS18B20andpull-upresistors,connected with jumper wiresthrough Breadboardaccording to the program algorithm. In addition, relevant component specifications are concisely provided upon which schematic connection diagram was generated. Lastly,theaimofthisstudywasto builda platform for sensor with data loggingability in order to achieve excellent performance at substantially lower coststhen currently available ones on the market.. Article history: Received (11.12.2017); Revised (09.01.2018); Accepted (30.01.2018)